VALIDITY OF STUDENT WORKSHEET BASED ON ROLE PLAYING IN HUMAN EXCRETORY SYSTEM MATERIAL TO IMPROVE MOTIVATION AND LEARNING OUTCOMES - Nadhia Al Hamani; Siti Nurul Hidayati (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to describe the validity of student worksheet based on role playing in human excretory system to increase motivation and learning outcomes. The method used is the validation method with the instrument in the form of a validation sheet. The results of the study were obtained from the results of validation by two science lecturers and one junior high school science teacher where in the didactic requirements get a mode score of 4 with a valid criteria, the construction requirements get score of 4 with a valid criteria, the technical requirements get score of 5 with a very valid criteria and the suitability aspect with role playing models get a score of 4 with valid criteria. Based on the results of these studies, it can be concluded that student worksheet based on role playing is valid to trying out to improve motivation and learning outcomes.Keywords: Student worksheets, role playing, motivation, learning outcomes